Research of Organization and Administration: analysis in Guidance and Counseling - Evi Fitriyanti (Asosiasi Asesmen Pendidikan (AAP), 2025)
The management of guidance and counseling services in schools is strongly influenced by the existence of a structured organization, well-organized administration, and systematic managerial mechanisms. This study aims to examine how organizational elements, administrative systems, personnel roles, and managerial functions interact to support effective and sustainable guidance and counseling services. This study used a literature study method by reviewing scientific books, research journals, guidance and counseling service guidelines, and relevant academic documents. Data were analyzed using content analysis techniques by classifying concepts, synthesizing theories, and drawing conceptual conclusions. The findings highlight that clear organizational structures, professional administration, and integrated management functions planning, organizing, implementing, and monitoring play a crucial role in ensuring the quality and continuity of guidance and counseling services.